Potential Pitfall in the Assessment of Lung Cancer with FDG-PET/CT: Talc Pleurodesis Causes Intrathoracic Nodal FDG Avidity. (25th May 2013) - Wang, Yingbing; Carter, Brett W.; Muse, Victorine; Digumarthy, Subba; Shepard, Jo-Anne; Sharma, Amita
Abstract : Objective . Talc pleurodesis is a common procedure performed to treat complications related to lung cancer. The purpose of our study was to characterize any thoracic nodal findings on FDG PET/CT associated with prior talc pleurodesis. Materials and Methods . The electronic medical record identified 44 patients who underwent PET/CT between January 2006 and December 2010 and had a history of talc pleurodesis. For each exam, we evaluated the distribution pattern, size, and attenuation of intrathoracic lymph nodes and the associated standardized uptake value. Results . High-attenuation intrathoracic lymph nodes were noted in 11 patients (25%), and all had corresponding increased FDG uptake (range 2–9 mm). Involved nodal groups were anterior peridiaphragmatic (100%), paracardiac (45%), internal mammary (25%), and peri-IVC (18%) nodal stations. Seven of the 11 patients (63%) had involvement of multiple lymph nodal groups. Mean longitudinal PET/CT and standalone CT followups of15 ± 11 months showed persistence of both high-attenuation and increased uptake at these sites, without increase in nodal size suggesting metastatic disease involvement. Conclusions . FDG avid, high-attenuation lymph nodes along the lymphatic drainage pathway for parietal pleura are a relatively common finding following talc pleurodesis and should not be mistaken for nodal metastases during the evaluation of patients with history of lung cancer.